Legal Protection For Children Againts Sexual Exploitation and Abuse of Children Online - Wijakusumariasih, Ni Putu Ika (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 8 No 1 (2019), 2019)
The disclosure of cases of pedophiles online on social media in Indonesia certainly dangers that lurk children from perpetrators of sexual crimes. End Child Prostitution in Asian Tourism (ECPAT) Indonesia and the Criminal Crime Reform Institute (ICJR) regard this case of online child pornography as the largest ever disclosed by police without casualties. Online pedophile actors operating on social media Facebook use Official Candy Group accounts. Online pedophile prostitution has involved international networks. Departing from this background, the purpose of writing this scientific paper is to find out about the protection of children in Indonesia in terms of online pedophiles that refer to international child protection instruments that have been ratified. The research method used in this study is a normative legal research method. Seeing the situation in the territory of Indonesia become a place of practice that deviates until the involvement of international syndicates and modes is more sophisticated. Conditions further strengthen the assumption that Indonesia is indeed in an emergency of sexual violence. Harmonizing national laws to protect children online with international standards is key to providing the right tools for law enforcement in dealing with child sex crimes. In the child protection survey in the digital era in ASEAN member countries, it appears that Indonesia still needs improvement in terms of legal instruments related to child protection in the context of regulations and policies in making child protection mechanisms in the virtual realm in accordance with global commitments in which Indonesia is member of several international organizations.